Activation of a PARACEST Agent for MRI through Selective Outersphere Interactions with Phosphate Diesters - Huang, Ching-Hui (2010)
Ln(S-THP)(3+) complexes are paramagnetic chemical exchange saturation transfer agents (PARACEST) agents for magnetic resonance imaging (MRI) (S-THP = (1S,4S,7S,10S)-1,4,7,10-tetrakis(2-hydroxypropyl)-1,4,7,10-tetraazacyclododecane, Ln(III) = Ce(III), Eu(III), Yb(III)). CEST spectra at 11.7 T show that the PARACEST effect of these complexes is enhanced at neutral pH in buffered solutions containing 100 mM NaCl upon addition of 1–2 equivalents of diethylphosphate (DEP). CEST images of phantoms at 4.7 T confirm that DEP enhances the properties of Yb(S-THP)(3+) as a PARACEST MRI agent in buffered solutions at neutral pH and 100 mM NaCl. Studies using (1)H NMR, direct excitation Eu(III) luminescence spectroscopy, and UV-visible spectroscopy show that DEP is an outersphere ligand. Dissociation constants for [Ln(S-THP)(OH(2))](DEP) are 1.9 mM and 2.8 mM for Ln(III) = Yb(III) at pH 7.0 and Eu(III) at pH 7.4, respectively. Related ligands including phosphorothioic acid, O,O-diethylester, ethyl methylphosphonate, O-(4-nitrophenylphosphoryl)choline and cyclic 3,5-adenosine monophosphate do not activate PARACEST. BNPP (bis(4-nitrophenyl phosphate) activates PARACEST of Ln(S-THP)(3+) (Ln(III) = Eu(III), Yb(III)), albeit less effectively than does DEP. This data shows that binding through second coordination sphere interactions is selective for phosphate diesters with two terminal oxygens and two identical ester groups. A crystal structure of [Eu(S-THP)(OH(2))]((O(2)NPhO)(2)PO(2))(2)(CF(3)SO(3)) · 2H(2)O · iPrOH has two outersphere BNPP anions that form hydrogen bonds to the alcohol groups of the macrocycle and the bound water ligand. This structure supports (1)H NMR spectroscopy studies showing that outersphere interactions of the phosphate diester with the alcohol protons modulate the rate of alcohol proton exchange to influence the PARACEST properties of the complex. Further, DEP interacts only with the non-ionized form of the complex, Ln(S-THP)(OH(2))(3+) contributing to the pH dependence of the PARACEST effect.